An Asymmetric Hygroscopic Structure for Moisture‐Driven Hygro‐Ionic Electricity Generation and Storage. Issue 21 (27th April 2022) - Zhang, Yaoxin; Guo, Shuai; Yu, Zhi Gen; Qu, Hao; Sun, Wanxin; Yang, Jiachen; Suresh, Lakshmi; Zhang, Xueping; Koh, J. Justin; Tan, Swee Ching
Abstract: The interactions between moisture and materials give rise to the possibility of moisture‐driven energy generation (MEG). Current MEG materials and devices only establish this interaction during water sorption in specific configurations, and conversion is eventually ceased by saturated water uptake. This paper reports an asymmetric hygroscopic structure (AHS) that simultaneously achieves energy harvesting and storage from moisture absorption. The AHS is constructed by the asymmetric deposition of a hygroscopic ionic hydrogel over a layer of functionalized carbon. Water absorbed from the air creates wet‐dry asymmetry across the AHS and hence an in‐plane electric field. The asymmetry can be perpetually maintained even after saturated water absorption. The absorbed water triggers the spontaneous development of an electrical double layer (EDL) over the carbon surface, which is termed a hygro‐ionic process, accounting for the capacitive properties of the AHS. A peak power density of 70 µW cm ‐3  was realized after geometry optimization. The AHS shows the ability to be recharged either by itself owing to a self‐regeneration effect or via external electrical means, which allows it to serve as an energy storage device. In addition to insights into moisture‐material interaction, AHSs further shows potential for electronics powering in assembled devices. Abstract : An unusual route for moisture‐driven energy generation (MEG) is proposed by an asymmetric hygroscopic structure (AHS), which simultaneously achieves MEG and energy storage. The water‐absorption triggered dual function originates from the permanently maintained wet‐dry asymmetry that is formed across the AHS by the asymmetric deposition of a hygroscopic ionic hydrogel over a functionalized‐carbon layer.